THE IMPACT OF CLIMATE CHANGE ON ENVIRONMENTAL DISPUTES AND CONFLICTS IN INDONESIA - Yusuf, M (Communale Journal, 2023)
Climate change is a critical issue in Indonesia with significant environmental and societal consequences. This research explores the impact of climate change in the context of ecological disputes and conflicts in Indonesia. Involving multidimensional analysis, this study investigates how climate change exacerbates tensions between natural resource utilization and environmental conservation. The results show that rising temperatures, changes in rainfall patterns, and rising sea levels significantly contribute to natural resource conflicts. A deeper understanding of these dynamics will enable the formulation of more effective policies to manage and prevent disputes while promoting environmental sustainability in the future. This study provides a local nuanced view of the global challenge of climate change and provides a basis for mitigation and adaptation efforts in Indonesia. This research investigates the impact of climate change on environmental disputes and conflicts in Indonesia. As a tropical country vulnerable to climate change, Indonesia faces severe challenges in balancing economic development and ecological conservation. The impacts of climate change, such as rising temperatures, changes in rain patterns, and rising sea levels, are triggering conflicts related to land, natural resources, and the rights of indigenous peoples. This research uses an interdisciplinary approach to analyze the complex relationship between climate change and environmental conflict, focusing on case studies in various regions of Indonesia. The results are expected to provide in-depth insights for public policy and sustainable mitigation actions to overcome the impacts of climate change and minimize the risk of environmental conflicts in the future.